IMPLEMENTASI KEBIJAKAN HUTAN KEMASYARAKATAN (Studi Kasus Hutan Kemasyarakatan di Dusun Kalibiru, Kulon Progo) - , Taufiqurrohman, Dr. Erwan Agus Purwanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study discusses the implementation of community forestry programs (HKm) in Kalibiru, Kulon Progo is motivated by the success of KTHKm Mandiri utilize community forestry permits to improve the welfare of the community without destroying the forest. Otherwise, the programs under social forestry policy in general have failed, and the realization of the goal of adopting a national community forest area is only 10,49% yet. This study aims to determine the implementation process of community forestry programs in Kalibiru and determine the factors that influence the success of its implementation. This study is expected to be one of the cases of successful community forest and may be a lesson to HKm development in other places. This study used a qualitative approach method with inductive analysis, and presented in a descriptive form. Data was collected through interviews, field observations, and document study. The results obtained show that the implementation process begins with good socialization by NGOs companion so that people become excited and enthusiastic oversee the implementation of a participatory process. Successful implementation of community forestry programs in Kalibiru influenced by factors : 1) the policy environment factor in the form of the role of NGOs, characteristics and support of the target group, and the disposition of the Regent. 2) availability of resources including human resources and financial resources and 3) Accuracy of policy instrument. This study suggested that forestry programs aimed at community empowerment so as to achieve self-sufficiency in managing the challenges and potential management of existing resources.